U.S. service exports and foreign barriers : an agenda for negotiations - Stalson, Helena; NPA Committee on Changing International Realities (Washington, D.C. : National Planning Association, Committee on Changing International Realities, 1985)
This book explains some of the U.S service trade barriers for foreign exports. It examines the significance of foreign trade for services; the problem of measurement position of the US in global services trade; profile of barriers to services; the US presence abroad; services and their implications for employment among other issues.
Spine title: U.S. service exports & foreign barriers.
Bibliography: p. 103-107.
as; 25/01/19
Loans
Keywords: Service industries; United States